Case Report: Identification of the First Synonymous Variant of Myosin Binding Protein C3 (c.24A>C, p.P8P) Altering RNA Splicing in a Cardiomyopathy and Sudden Cardiac Death Case - Jin, Jie-Yuan; Xiao, Jiao; Dong, Yi; Sheng, Yue; Guo, Ya-Dong; Xiang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Background: Sudden cardiac death (SCD), based on sudden cardiac ejection cessation, is an unexpected death. Primary cardiomyopathies including dilated cardiomyopathy (DCM), are one of main causes of SCD. DCM is characterized by cardiac dilatation and reduced systolic function, with a prevalence in adults of 1/250. DCM has been reported more than 60 disease-causing genes, and MYBPC3 variants are one of the most common and well-known causes of DCM. Methods: We identified a 29-year-old female died of SCD. We preformed whole-exome sequencing (WES) to detect her genetic etiology and used minigene modeling and immunohistochemistry staining to verify the pathogenicity. Results: We determined that the woman was died of SCD caused by DCM, and identified a novel synonymous variant in MYBPC3 (NM_000256.3: c.24A>C, p.P8P) in the deceased. The variant can result in abnormal splicing, which was confirmed by minigene models and immunohistochemistry staining. Conclusion: We might identify the first synonymous variant in MYBPC3 in a SCD case and verified its pathogenicity. Our description enriched the spectrum of MYBPC3 variants and emphasized the significance of synonymous variants which are always disregarded in genetic screening.